2017
DOI: 10.1212/wnl.0000000000003784
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral measures of cortical hyperexcitability assessed in people who experience visual snow

Abstract: Our study demonstrates that visual perceptual measures involving the suprathreshold processing of contrast and luminance are abnormal in a group of individuals with visual snow. Our data are consistent with elevated excitability in primary visual cortex; however, further research is required to provide more direct evidence for this proposed mechanism. The ability to measure perceptual differences in visual snow reveals promise for the future development of clinical tests to assist in visual snow diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 35 publications
2
60
0
Order By: Relevance
“…The present results were consistent with those in previous studies. 2,4 Flickering and floaters were present in all VS patients. Nyctalopia was frequently reported by VS wom patients, but no statistically significant differences were observed.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The present results were consistent with those in previous studies. 2,4 Flickering and floaters were present in all VS patients. Nyctalopia was frequently reported by VS wom patients, but no statistically significant differences were observed.…”
Section: Discussionmentioning
confidence: 91%
“…A previous functional brain imaging study revealed hypermetabolism of the supplementary visual cortex in VS patients . In a recent study, abnormal visual perceptual measures and elevated excitability in the primary visual cortex were observed in VS patients . In our study, using TMS induced magnetophosphene thresholds, we also demonstrated the occipital cortex hyperexcitability in VS patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations